Artisanal fishing, shrimp farming and mangroves: perspectives on the Federal Law nº 12651/2012 and the use of “apicum” and “salgado” areas in Canguaretama/RN, Brazil - Lima, Thaís Bezerril Brandão de; Silva, Márcia Regina Farias da; Carvalho, Rodrigo Guimarães de (Sociedade & Natureza, 2019)
This paper presents considerations on the Federal Law nº 12651/2012, better known as Brazil’s new Forest Code, which granted the use of “apicum” (swamp in the Tupi language)” and “salgado” sectors (regions of mangrove) to shrimp farming. This code approved that 35% of these ecotones can be used for shrimp farming. Thus, this study aimed to look into the way these legislative updates have influenced or will influence the social, economic and environmental aspects of the shrimp farming activity in Rio Grande do Norte (RN), particularly in the municipality of Canguaretama. A quali-quantitative approach was used, with questionnaires and semi-structured interviews applied to the artisanal fishermen, shrimp farmers and to the State Environmental Agency. Artisanal fishermen understood that this legislative change degrades and unbalances the ecological environment, especially that there will be loss of territory and damage to their fishing resources, so they were against such change, the same opinion of the State Environmental Agency. On the other hand, shrimp farmers were in favor of the changes, claiming to be a legal incentive for their activity, contributing to the legalization of previously illegal enterprises, in addition to expanding their area of cultivation.